EVALUATION OF THE EFFECTIVENESS OF AMOXICILLIN IN THE PHARMACOTHERAPY OF RECURRENT BRONCHITIS IN CHILDREN (World Bulletin of Social Sciences, 2026)
Evaluation of the effectiveness of amoxicillin depending on the severity of the disease, complications and concomitant pathology in children undergoing inpatient treatment at the TSMU clinic.
Keywords: Lower respiratory tract diseases; recurrent obstructive bronchitis; etiotropic treatment